Intention to Visit Eco-Friendly Destinations for Tourism Experiences: An Extended Theory of Planned Behavior - --, Sujood; Hamid, Sheeba; Bano, Naseem (Journal of Tourism, Sustainability and Well-being, 2021)
The purpose of this study is to investigate consumers’ intentions to visit eco-friendly destinations for tourism experiences by developing an integrated structural model that incorporates the TPB model with an additional construct, i.e. environmental friendly activities (EFA). Data was collected via a web-based survey and then analyzed. The related hypotheses have been tested using Structural Equation Modeling (SEM). The sample consists of 471 responses from Indian consumers. The findings reveal that attitude, subjective norm, perceived behavioral control and environmental friendly activities are significant predictors of intention. These constructs explained approximately 50 percent of the variance in the intention. The results of this study contribute to the body of the knowledge of intention, eco-friendly destinations, and tourism experiences and also provide useful information for developing effective marketing strategies to encourage consumers to visit eco-friendly destinations for tourism experiences. To the best of the researchers’ knowledge, this was the first attempt to predict the intention to visit eco-friendly destinations for tourism experiences by employing TPB along with the EFA construct.